Maternity Wear Preferences, Problems, and Expectations of Pregnant Women of Pakistan - Rashid, Hina; Saeed, Ayesha; Abiodullah, Muhammad (Journal of Design and Textiles, 2024)
Pregnant women tend to experience fast, non-linear anthropometric changes, especially in their chests, abdomen, and hips during the periods following gestation. Research has shown that physical changes get more prominent in the 2nd and 3rd trimester of pregnancy. However, the present Pakistani apparel market does not cater to the clothing needs of pregnant women who are compelled to choose plus-size garments to cater and camouflage their body changes. Interviews were conducted to understand and design the maternity garment requirements, problems, preferences, and expectations of Pakistani pregnant women. To obtain the desired in-depth information, open-ended questions were asked. The information collected was analyzed through qualitative analysis and themes were generated. The results reflected preference towards loose-fitted, breathable, and highly absorbent single layered garments which could cover their body silhouettes. The pregnant women disapproved highly embellished, fitted, and multilayered synthetic-based garments. However, they desired to wear stylish and innovative outfits, designed within the boundary of cultural and religious norms.